Physico-chemical and microbiological qualities of locally produced raw goat milk - Lai, C. Y.; Abu Bakar, Fatimah; Mahyudin, Nor Ainy; Saari, Nazamid; Zaman, Muhammad Zukhrufuz (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Raw goat milk is recognized as one kind of nutritious food owed to its originality and medicinal values. This study aimed to evaluate the physico-chemical and microbiological qualities of locally produced raw goat milk prior any processing steps during storage. Milk samples passed organoleptic test and C.O.B. test were mostly (88.89 %) failed in alcohol test. AOAC Official method of oven drying method, Kjeldahl method and Soxhlet method were performed in physico-chemical analysis where results obtained were partially in lined with reported literature due to subjective factors of breeds, geographical areas and feeds. The locally produced raw goat milk's compositions are high in water content and low in fat percentage. Initial total plate count, coliform count and proteolytic count tested were 3.44 log cfu/ml, 1.87 log cfu/ml and 1.97 log cfu/ml, respectively. Storage time showed significant effect on the bacterial counts (p > 0.05) of milk samples. Shelf-life of milk samples were kept up to 12 hours under ambient temperature (3.95 log cfu/ml) had not exceeded the standard limit. The shelflife of the milk samples were extended up to 16 days storage under refrigerated temperature of 4°C. The microbiological quality of the milk samples showed a significant bacteriological growth upon prolonged storage and high initial coliform count indicates possible poor hygienic practices at farm level.